Extraction and Identification of saponin extracts from Lepidium aucheri Boiss and antifungal properties evaluation - Alkhuzaie, Mohammad; Kredy, Husam; Guzar, Sajid; Charfeddine, Bassem; Ines , Ouahchi (University of Thi-Qar Journal of Science, 2024)
The analysis by High-performance liquid chromatography (HPLC) revealed that the saponin extracts contain a significant component called (Hederagenin glycoside). The wavelengths and electronic transitions of the active groups of the saponin extract were also determined using the UV-Vis Spectra. The optimal result was obtained by utilizing the Gemini C18 (5 µm) stationary phase manufactured by Phenomenex. They determine the optimal chromatographic conditions for enhancing LC/MS analysis by evaluating several mobile phases on a reversed-phase C18 column.  Illustrates the anticipated patterns of fragmentation observed in the mass spectra of substances. The Antifungal activity against Aspergillus flavus, Aspergillus Niger, and Aspergillus Alternaria was determined. The inhibitory effect in vitro was defined to appear, triterpenoid saponins extract showed maximum growth activity inhibitory of fungi against pathogens like Aspergillus Alternaria and Aspergillus Niger (2 cm), at the concentration (100 ppm) and the minimum growth activity inhibitory was against Aspergillus Alternaria (5 cm) at a concentration (25 ppm) compare with control. The triterpenoid saponins extract its ability to grow activity inhibition of fungi type Aspergillus Alternaria, Aspergillus Niger. On the other hand, the percentage of hemolysis activity in human blood increases with a high concentration of triterpenoid Saponins extract.